2008
DOI: 10.1029/2008gl034714
|View full text |Cite
|
Sign up to set email alerts
|

Foliar uptake of atmospheric organic nitrates

Abstract: [1] Increasing nitrogen deposition to forests can impact the balance between the carbon and nitrogen cycles. This nitrogen source, if taken up and used by forests, can increase growth and carbon storage. While previous findings have suggested that nitrogen deposition is not an important source of nitrogen for a forest ecosystem, the possibility of canopy uptake was not considered. Foliar uptake and utilization of inorganic nitrogen, such as NO 2 and NH 3 , has been shown to occur, but utilization of organic ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…The data demonstrate that organic nitrogen is an important fraction of the oxidized nitrogen dry deposition flux, similar to wet deposition (85). The organic nitrogen may be taken up by foliage (86,87) and incorporated into the synthesis of leaf nutrients. As the effects of organic nitrogen on carbon sequestration are inadequately represented in most ecological models, these data motivate further inquiry into the ecosystem ramifications of OVOC deposition.…”
Section: Resultsmentioning
confidence: 78%
“…The data demonstrate that organic nitrogen is an important fraction of the oxidized nitrogen dry deposition flux, similar to wet deposition (85). The organic nitrogen may be taken up by foliage (86,87) and incorporated into the synthesis of leaf nutrients. As the effects of organic nitrogen on carbon sequestration are inadequately represented in most ecological models, these data motivate further inquiry into the ecosystem ramifications of OVOC deposition.…”
Section: Resultsmentioning
confidence: 78%
“…The measured Henry's law coefficients of some of the more soluble individual hydroxy nitrates (∼ 10 3 -10 5 M atm −1 , Shepson et al, 1996;Treves et al, 2000) are orders of magnitude lower than that of HNO 3 (1 × 10 14 M atm −1 at pH ∼ 6.5, Seinfeld and Pandis, 2006). Still, these measured Henry's law coefficients of hydroxy nitrates indicate that wet deposition is a significant loss process and a recent study indicates that foliar uptake of organic nitrates is possible (Lockwood et al, 2008 Min, personal communication, 2012). Although the exact magnitude of the depositional loss likely depends on the specific composition of ANs, as well as the partitioning between gas and aerosol, we assume that a similar result exists for the boreal forest since recent measurements of speciated organic nitrates using chemical ionization mass spectrometry at the ponderosa pine forest (Beaver et al, 2012) indicate a similar composition of ANs as assumed here from the instantaneous production rate.…”
Section: Depositionmentioning
confidence: 65%
“…Since many areas are nitrogen limited, introduction of nitrogen will also affect the carbon storage capacity of an ecosystem (e.g., Holland et al, 1997;Thornton et al, 2007Thornton et al, , 2009Bonan and Levis, 2010). A recent study observed the direct foliar uptake of RONO 2 and subsequent incorporation of the nitrogen into amino acids (Lockwood et al, 2008), indicating that (at least some) RONO 2 will affect plant growth.…”
Section: Discussionmentioning
confidence: 99%